Analisis Sumber Informasi dan Pengetahuan dengan Praktik Swamedikasi: Analysis of Information Sources and Knowledge with Self-Medication Practices - Susanto, Agus; Purwantiningrum, Heni; Sari, Meliyana Perwita (Jurnal Sains dan Kesehatan, 2024)
Self-medication is often a problem caused by a poor knowledge of drugs and usage. Problems related to self-medication are also related to information sources as a reference in drug selection and self-medication practices. The objective of the research was to analyze the relationship of information and knowledge with self-medication practices. The research approach used was cross sectional. Sample size was 344 people aged at least 18 years and at least do self-medication twice a year. Selection of research samples used accidental sampling method. Field data collection was done by questionnaire. Data analysis was descriptive and cross tabulation. Chi-Square test was used to test the relationship at the 0.05 level of significance. Source of information from advertisements 48%, good knowledge 59.6%, and moderately good self-medication practices 73%. P-value of information source was 0.023 and knowledge was 0.378. Information sources are related to self-medication practices.   Keywords:          Information resources, Knowledge, Self-medication   Abstrak Swamedikasi sering kali menjadi masalah karena kurangnya pemahaman tentang obat dan penggunaannya. Masalah terkait swamedikasi juga berkaitan dengan sumber informasi sebagai acuan dalam pemilihan obat dan praktik swamedikasi. Tujuan dari penelitian ini adalah untuk menganalisis hubungan antara informasi dan pengetahuan dengan praktik pengobatan mandiri. Pendekatan yang digunakan dalam penelitian ini adalah potong lintang (cross sectional). Sampel penelitian sebesar 344 orang berusia minimal 18 tahun dan minimal melakukan swamedikasi dua kali dalam setahun. Pemilihan sampel penelitian menggunakan metode accidental sampling. Pengumpulan data lapangan menggunakan kuesioner. Analisis data dilakukan secara deskriptif dan tabulasi silang. Uji hubungan dengan uji Chi-Square pada taraf kemaknaan 0,05. Sumber informasi dari iklan 48%, pengetahuan cukup baik 59,6%, dan praktik swamedikasi baik 73,0%. P-value sumber informasi 0,023 dan pengetahuan 0,378. Sumber informasi berhubungan dengan praktik swamedikasi.   Kata Kunci:         Sumber informasi, Pengetahuan, Praktik swamedikasi